Respuesta :
-2z - xy = z + 7
You are solving for x. Note the equal sign. What you do to one side, you do to the other. Isolate the x.
First, add 2z to both sides
-2z (+2z) - xy = z + 7 (+2z)
Simplify. Combine like terms
-xy = z + 2z + 7
-xy = 3z + 7
Completely isolate the x. Divide -y from both sides
(-xy)/-y = (3z + 7)/-y
x = (3z + 7)/-y
Simplify
z = (3z + 7)/(-y) is your answer
hope this helps
[tex]-2z-xy=z+7\ \ \ \ |+2z\\\\-xy=3z+7\ \ \ \ |:(-y)\neq0\\\\x=\dfrac{3z+7}{-y}\\\\\boxed{x=-\dfrac{3z+7}{y}}[/tex]